Optimizing isotropic three‐dimensional fast spin‐echo methods for imaging the knee. Issue 6 (29th October 2013) - Li, Charles Q.; Chen, Weitian; Rosenberg, Jarrett K.; Beatty, Philip J.; Kijowski, Richard; Hargreaves, Brian A.; Busse, Reed F.; Gold, Garry E.
Abstract : Purpose: To optimize acquisition parameters for three‐dimensional fast spin‐echo (3D FSE) imaging of the knee. Materials and Methods: The knees of eight healthy volunteers were imaged in a 3 Tesla MRI scanner using an eight‐channel knee coil. A total of 146 intermediate‐weighted isotropic resolution 3D FSE (3D‐FSE‐Cube) images with varied acquisition parameter settings were acquired with an additional reference scan performed for subjective image quality assessment. Images were graded for overall quality, parallel imaging artifact severity and blurring. Cartilage, muscle, and fluid signal‐to‐noise ratios and fluid‐cartilage contrast‐to‐noise ratios were quantified by acquiring scans without radiofrequency excitation and custom‐reconstructing the k ‐space data. Mixed effects regression modeling was used to determine statistically significant effects of different parameters on image quality. Results: Changes in receiver bandwidth, repetition time and echo train length significantly affected all measurements of image quality ( P < 0.05). Reducing bandwidth improved all metrics of image quality with the exception of blurring. Reader agreement was slight to fair for subjective metrics, but overall trends in quality ratings were apparent. Conclusion: We used a systematic approach to optimize 3D‐FSE‐Cube parameters for knee imaging. Image quality was overall improved using a receiver bandwidth of ±31.25 kHz, and blurring increased with lower bandwidth and longer echo trains.J. Magn. Reson. Imaging 2014;39:1417–1425 . ©2013 Wiley Periodicals, Inc .